Evaluasi dan Perbaikan Antarmuka Pengguna Aplikasi Mobile Tulungagung Tourism dengan Metode Usability Testing dan User Experience Questionnaire (UEQ) - Edo Yokko Rolando; Herman Tolle; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Tulungagung Tourism mobile application is an application in the field of tourism under the auspices of the Office of Culture and Tourism of Tulungagung Regency. This application is useful for tourists who come from Tulungagung or even from outside Tulungagung, to find out information and recommendations about tourist spots in Tulungagung. An application must certainly have good usability so that users will have good experience when using an application, and user experience can be said to be very important for an application. Different on the Tulungagung Tourism mobile application. This application has problems related to usability such as users not getting the output they expect when operating the application. In this study, analyzing a level of usability based on user experience in applications using the usability testing method to measure aspects of effectiveness and efficiency, then user experience questionnaire (UEQ) to measure the level of satisfaction (satisfaction). Later this study produced a new interface recommendation in the form of a prototype. From the evaluation results resulted in an increase in effectiveness aspects of 5.38%, efficiency aspects increased by 34.93%, and aspect satisfaction increased by 20%. For the stimulation scale results, which initially were good, rose to excellent, then on a novelty scale that initially above average rose to good. With these results it can be concluded that the user experience in the application increases.